Increased risk of A(H1N1)pdm09 influenza infection in UK pig industry workers compared to a general population cohort - Fragaszy, Ellen; Ishola, David A.; Brown, Ian H.; Enstone, Joanne; Nguyen-Van-Tam, Jonathan S.; Simons, Robin; Tucker, Alexander W.; Wieland, Barbara; Williamson, Susanna M.; Hayward, Andrew C.; Wood, James L.N. (Wiley, 2016)
Background: Pigs are mixing vessels for influenza viral reassortment but the extent of influenza transmission between swine and humans is not well understood.